Pengaruh Abu Terbang Batubara dan Tandan Kosong Kelapa Sawit terhadap pH, Eh serta Fe-Larut pada Lahan Sulfat Masam - Adam Febrius Udatama; Bambang Joko Priatmadi; Gusti Irya Ichriani (Acta Solum, 2024)
The issue of acid sulfate soil in Indonesia, characterized by high acidity due to pyrite (FeS2) oxidation, produces sulfuric acid and iron oxide detrimental to agricultural productivity. The use of ameliorants such as coal fly ash (ATB) and empty oil palm bunches (TKKS) is expected to improve soil chemical conditions. The study aims to assess the impact of the ATB and TKKS combination on increasing pH, lowering Eh, and reducing soluble Fe concentration in acid sulfate soils, determining the most effective dose. The research method employs completely randomized design (CRD) with various doses of a combination of ATB and TKKS applied to acidic sulfate soil. Observations focus on changes in pH, redox potential (Eh), and soluble Fe concentration post-treatment. Results of study indicated that application of the ATB and TKKS combination given significant effect to increase soil pH and decreased Eh values. Certain dose combinations exhibit higher effectiveness than single treatments. In conclusion, the combined use of ATB and TKKS offers an efficient and environmentally friendly solution to acidity and iron solubility issues in acidic sulfate soils, supporting increased agricultural land productivity.